Hoya species of Belitung Island, Indonesia, utilization and conservation - SRI RAHAYU; YULIAN FAKHRURROZI; HIRMAS FUADY PUTRA (Society for Indonesian Biodiversity, 2018)
Rahayu S, Fakhrurrozi Y, Putra HF. 2018. Hoya species of Belitung Island, Indonesia, utilization and conservation. Biodiversitas 19: 369-376. Epiphyte greatly contributing to the forest biomass in the tropic. Heath forest as occurred in Belitung Island, Indonesia is a specific habitat for many endemic species, which are poor in nutrients and very fragile in response to any disturbance. We observed Hoya species-one of the epiphytic genus in the tropic in the heath forest and on other habitats of Belitung Island, Indonesia. Hoya species are plants with promising uses as functional ornamental plants (able to absorb pollutants from their growing environments), and as sources of certain medicinal and pharmaceutical compounds. A survey of Hoya was carried out on Belitung Island, off the southeast coast of Sumatra, in 2015, 2016 and 2017. There are two interesting Hoya species that grow well in the